MARTABAT ALAM TUJUH DALAM PERSPEKTIF SYEKH ABDUL MUHYI PAMIJAHAN - A Lukman Hamid; Dendi Yuda S (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
Sheikh Abdul Muhyi is a cleric who spreads Islam in the southern region of West Java. Born in Mataram in 1650 AD/1071 H and raised by his parents in the city of Gresik. As a propagator of Islam, he has written works that become a reference in his da'wah. One of his works is a manuscript entitled Martabat Kang Pitutu (dignity of the seven realms). Among researchers, this paper is still debatable, whether it is the original work or in the form of an adaptation of a previously existing work with a certain interpretation from it. This study seeks to find answers to what and how the teachings of the seven natural dignity of Sheikh Abdul Muhyi's perspectives are taught and why the seven natural dignity teachings are taught/what is its significance. This is done because the teachings of the seven natural dignity in the world of Sufism originated from the teachings of Sufism wahdatul form (unity of being) which was developed by Ibn Arabi. It is not clear when this teaching first entered Indonesia. What is clear is that before Sheikh Haji Abdul Muhyi, several Indonesian Sufi scholars had written this teaching, such as Hamzah Fansuri, Syamsuddin as-Sumatrani w. 1630 and Abdur Rauf Singkel w. 1615 with their respective derivations and variations. Based on the results of this study, it was found that the teachings of the dignity of the seven Sheikh Abdul Muhyi have conformity with the teachings of the dignity of the other seven. What distinguishes it is the written language and contextualization of teachings in accordance with the Indonesian spirit